Formulasi Sediaan Krim Menggunakan Kolagen Tulang Itik Air (Anas platyrhynchos domesticus) Sebagai Anti Aging - Sudewi Sudewi; Nilsya Febrika Zebua; Aulia Milda (Forum Kerjasama Pendidikan Tinggi (FKPT), 2020)
The collagen content in the human body decreases with age. One solution to reduce these negative effects is the application of collagen in various cosmetic and medicinal products. In the bones contain a lot of collagen and one of them is found in the water duck bone that has not been treated and is the result of waste. This study aims to make an anti- aging cream preparation resep from water duck bone collagen that can eliminate wrinkles, blemishes, shrink pores and smooth the skin. This research uses an experimental method using water duck bone test material. Stages of research include extraction of collagen from water duck bone, collagen characterization by infra red spectrophotomenter, making anti- aging cream of water duck bone with concentrations of 1%, 1. 5%, 2. 5%, 3. 5%, formulation and evaluation of cream preparations and test the ability of preparations using a skin analyzer. The results showed that the water duck bone contained collagen at wave numbers 3280- 3380 cm- 1 and 1280- 1680 cm- 1 which indicated the presence of amine and amide groups. Water duck bone collagen can be formulated into cream preparations with the evaluation results of preparations are homogeneous, stable and non- irritating preparations with a pH range of 6. 1 to 6. 4. Test results from collagen cream preparations show that the higher the concentration of collagen added to the resep, the more it will show a significant increase in effect.